2013
DOI: 10.1080/07055900.2013.791614
|View full text |Cite
|
Sign up to set email alerts
|

Glacier Meltwater Contributions and Glaciometeorological Regime of the Illecillewaet River Basin, British Columbia, Canada

Abstract: This study characterizes the meteorological parameters influencing glacier runoff and quantifies recent glacier contributions to streamflow in the Illecillewaet River basin, British Columbia. The Illecillewaet is a glacierized catchment that feeds the Columbia River, with terrain, glacial cover, and topographic relief that are typical of Columbia River headwaters basins in southwestern Canada. Meteorological and mass balance data collected on Illecillewaet Glacier are used to develop and constrain a distribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 51 publications
2
45
0
Order By: Relevance
“…We evaluated our method to isolate late summer flows from glacierized catchments against other empirical and physically based approaches. To evaluate our results against mechanistic modeling efforts at a high temporal resolution (daily), we compared our results to those of Hirose and Marshall () for the Illecillewaet basin for the melt years of 2009, 2010, and 2011. Hirose and Marshall () measured mass–balance and meteorological data from the Illecillewaet glacier from 2009 to 2011 and used a distributed hydrologic model to quantify glacier melt from all 79 glaciers from May 1 to September 14.…”
Section: Study Area and Methodsmentioning
confidence: 99%
“…We evaluated our method to isolate late summer flows from glacierized catchments against other empirical and physically based approaches. To evaluate our results against mechanistic modeling efforts at a high temporal resolution (daily), we compared our results to those of Hirose and Marshall () for the Illecillewaet basin for the melt years of 2009, 2010, and 2011. Hirose and Marshall () measured mass–balance and meteorological data from the Illecillewaet glacier from 2009 to 2011 and used a distributed hydrologic model to quantify glacier melt from all 79 glaciers from May 1 to September 14.…”
Section: Study Area and Methodsmentioning
confidence: 99%
“…Brock et al (2000) showed that these effects can be empirically approximated as a function of cumulative melt or maximum daily temperatures. This approach is adapted here to represent snow albedo decline through the summer melt season as a function of cumulative positive degree days, D d , after Hirose and Marshall (2013):…”
Section: Distributed Modelmentioning
confidence: 99%
“…(7) until the underlying surface is exposed again, after which albedo is set to be equal to its pre-freshened value. Summer precipitation events are modelled as random events, with the number of events from May through September, N P , treated as a free variable (Hirose and Marshall, 2013). The amount of daily precipitation within these events is modelled with a uniform random distribution varying from 1 to 10 mm.…”
Section: Distributed Modelmentioning
confidence: 99%
“…• C −1 on Morteratschgletscher, Switzerland (Klok and Oerlemans, 2004), and Illecillewaet Glacier, British Columbia (Hirose and Marshall, 2013), −0.68 ± 0.05 m w.e.…”
Section: Haig Glacier Energy Balance Sensitivities and Feedbacksmentioning
confidence: 99%
“…The snowpack thickness is initialized on 1 May of each year, set to the observed value measured during the annual winter mass balance survey. During the melt season, which is assumed to start after this date, seasonal snow albedo decreases as a function of cumulative positive degree days ( PDD) following Hirose and Marshall (2013):…”
Section: Surface Energy Balance and Melt Modelmentioning
confidence: 99%